2022
DOI: 10.1261/rna.079188.122
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of RNA-binding properties of the RNA helicase UPF1 by its activator UPF2

Abstract: The NMD helicase UPF1 is a prototype of the superfamily 1 (SF1) of RNA helicases that bind RNA with high affinity and translocate on it in an ATP-dependent manner. Previous studies showed that UPF1 has a low basal catalytic activity that is greatly enhanced upon binding of its interaction partner, UPF2. Activation of UPF1 by UPF2 entails a large conformational change that switches the helicase from an RNA-clamping mode to an RNA-unwinding mode. The ability of UPF1 to bind RNA was expected to be unaffected by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…In this UPF2-independent ‘branch’ of EJC-dependent NMD ( Figure 1 ), CASC3 is suggested to directly interact with eIF4A3, UPF3B as well as UPF1, with UPF3B binding to UPF1 and eRF3, thereby stabilising UPF1 in the vicinity of the EJC, despite of the lack of UPF2 [ 48 , 49 , 50 ]. In the canonical NMD pathway, UPF2 promotes UPF1’s ATPase and helicase activities and, thereby, supports NMD activation [ 51 , 52 , 53 ]. Recent studies have shed light on the mechanisms compensating for the absence of UPF2 in UPF2-independent NMD, revealing the involvement of serine/threonine-protein kinases AKT ( Figure 1 ) [ 54 , 55 ].…”
Section: Mammalian Nmd Pathwaysmentioning
confidence: 99%
See 4 more Smart Citations
“…In this UPF2-independent ‘branch’ of EJC-dependent NMD ( Figure 1 ), CASC3 is suggested to directly interact with eIF4A3, UPF3B as well as UPF1, with UPF3B binding to UPF1 and eRF3, thereby stabilising UPF1 in the vicinity of the EJC, despite of the lack of UPF2 [ 48 , 49 , 50 ]. In the canonical NMD pathway, UPF2 promotes UPF1’s ATPase and helicase activities and, thereby, supports NMD activation [ 51 , 52 , 53 ]. Recent studies have shed light on the mechanisms compensating for the absence of UPF2 in UPF2-independent NMD, revealing the involvement of serine/threonine-protein kinases AKT ( Figure 1 ) [ 54 , 55 ].…”
Section: Mammalian Nmd Pathwaysmentioning
confidence: 99%
“…Structural data of UPF1, in complex with the C-terminus of UPF2, shows that the CH domain of UPF1 is displaced upon UPF2-binding into an open conformation [ 52 , 79 ], resulting in decreased RNA-clamping and increased RNA-unwinding by UPF1 [ 51 , 52 ]. Recent biochemical and biophysical studies have shown that binding of UPF2 to UPF1 directly promotes dissociation of UPF1 from RNA in a non-competitive manner [ 53 ]. A low-resolution cryo-EM structure of the EJC, in complex with RNA and the three UPF proteins, shows that UPF1 is found in the vicinity of the RNA 3′-end [ 93 ].…”
Section: Core Nmd Factorsmentioning
confidence: 99%
See 3 more Smart Citations